Solve 2ax + 3by = a + 2b ; 3ax + 2by = 2a+b
Answers
Answered by
36
2ax + 3by = a + 2b
⇒ 2ax = a+2b – 3by
⇒ x = (a+2b-3by) / 2a
Put x in the second equation
3ax + 2by = 2a+b
⇒ 3a((a+2b-3by) / 2a) + 2by = 2a+b
By solving it,
we get
y = (4b-a)/5b
x = (a+2b-3by) / 2a x = (4a-b)/5a
⇒ 2ax = a+2b – 3by
⇒ x = (a+2b-3by) / 2a
Put x in the second equation
3ax + 2by = 2a+b
⇒ 3a((a+2b-3by) / 2a) + 2by = 2a+b
By solving it,
we get
y = (4b-a)/5b
x = (a+2b-3by) / 2a x = (4a-b)/5a
Answered by
14
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d30/b0b324b15b7820980ac3e9aee67bca97.jpg)
![](https://hi-static.z-dn.net/files/dc3/2b9c6908984c33b907f1a79d5c1468b8.jpg)
![](https://hi-static.z-dn.net/files/d65/45c6a09b95a795c5c3b20ecb27be4c94.jpg)
![](https://hi-static.z-dn.net/files/d57/aac55e6bc2784797051f6d5fdd0337ef.jpg)
Similar questions